Coronary CT Angiography for Coronary Artery Disease: The Current Status and Future Challenges - Saskia Dyah Handari (Heart Science Journal, 2023)
Coronary computed tomographic angiography, often known as CCTA, is quickly becoming the diagnostic technique of choice for determining the existence of coronary artery disease (CAD). In the future, CCTA may play an essential part as a "one-stop shop" in the screening, diagnosis, decision making, and treatment planning processes. Plaque burden, high-risk plaque, non-invasive angiography, perfusion with hyperemia, fractional flow reserve (FFR), percent of myocardium at risk, inflammation, myocardial scar, wall motion analysis, and risk scores are some of the many measures that are utilized.